Acoustic Enhancement of Polymer/ZnO Nanorod Photovoltaic Device Performance. (6th November 2013) - Shoaee, Safa; Briscoe, Joe; Durrant, James R.; Dunn, Steve
<x xml:space="preserve">Abstract</x> Acoustic vibrations are shown to enhance the photovoltaic efficiency of a P3HT/ZnO nanorod solar cell by up to 45%, correlated to a three‐fold increase in charge carrier lifetime. This is assigned to the generation of piezoelectric dipoles in the ZnO nanorods, indicating that the efficiency of solar cells may be enhanced in the presence of ambient vibrations by the use of piezoelectric materials. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>